The Role of Political Marketing in Enhancing the Perceived Image of the Candidate an Analytical Study of the Views of a Sample of Iraqi Society - Kadim, Jasim Rahi; Shaltag, Karim Hazen; Sabti, Yousif Mousa; Ali, Ghazanfar; Rizvi, Tamkinut; Atiyah, Mohsin Abdulameer; Abbas, Yasir Abdullah (South Asian Journal of Social Sciences and Humanities, 2021)
In light of the technological competition and modern marketing theories produced by globalization and the pursuit of the customer wherever he is, and the need to spread the principles and ideas that need laws, means and methods that govern them, devices, equipment and men specializing in the field of marketing to implement them, a new reality has emerged, which is the transfer of commercial marketing traditions to a new type of marketing. It is political marketing that deals with political events instead of dealing with goods and services and using them intelligently in achieving the required policy. It aims to name political symbols, increase financial aid and build a political program using the elements of the political marketing mix to reach a predetermined goal in order to employ the aspirations of public opinion, which has now occupied a wide place in contemporary democracies, especially in directing government systems and guiding their politicians to act in a specific way, and to take decisions that suit the broad public base. As a result, there has been an increase in interest in public opinion polls, which have become one of the features of life in modern democracies. The coordination process has also become clear between opinion research centers and decision-making centers to create harmony and harmony between decisions taken on various issues and public opinion trends towards them. In pursuit of the objectives of the study, a public opinion poll directed at a sample of Iraqi society was used on the practical side. On the theoretical side, a group of Arab and foreign sources, articles, and what was published on the Internet were used.